Edukasi Pemanfaatan Bahan Alam Sebagai Solusi Penanganan Penyakit Degeneratif pada Masyarakat Dusun Beji Sumberagung Bantul - Rusydan, Azka Muhammad; Lestari, Mardiana Puji; Veriarini, Falaisa Ananda; Elipitaloka , Naftali (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2025)
Hypertension is a chronic disease and a major risk factor for cardiovascular disease, often referred to as a "silent killer" due to its asymptomatic nature. Its prevalence in Indonesia is increasing, reaching 34.1% among individuals aged 18 years and over in 2018. Traditional herbal medicine can treat degenerative diseases, but its use is still limited due to inadequate public knowledge. This community service program aims to provide education about hypertension and the use of traditional herbal medicine in Dusun Beji, Bantul, Yogyakarta. The program includes health education, blood pressure checks, and promotion of herbal medicine for hypertension management. A total of 34 participants (85% attendance) attended the session, with 26 completing pretest and posttest questionnaires to evaluate increased knowledge. The majority of participants were elderly (?61 years, 50%) and female (69.2%), with 69.2% showing abnormal blood pressure levels. Educational materials, including presentations and brochures, were provided along with live demonstrations of herbal preparations. Post-test results showed a slight increase in mean score from 7.73 to 7.88, with increased homogeneity of data and an increase in median from 7 to 8. Although paired t-test showed no statistically significant difference (P=0.885), descriptive analysis showed an increase in understanding and awareness. Active participation during the discussion, especially regarding herbal preparations, reflected the community's interest in adopting alternative approaches to hypertension management. This initiative has succeeded in increasing awareness of hypertension and the benefits of herbal medicines to effectively manage the chronic disease and its complications.